Effects of Neuropeptide Substance P on Proliferation and β-Cell Differentiation of Adult Pancreatic Ductal Cells - Zhang, Nan; Gao, Di; Liu, Yudan; Ji, Sihan; Sha, Lei (Frontiers in Neuroscience, 2018)
Purpose The pancreas is innervated by sensory nerves, parasympathetic and sympathetic nerves. The classical neurotransmitters, acetylcholine and noradrenaline, and some kind of neuropeptides are contained in the terminals of these nerves. Neuropeptides substance P (SP) and calcitonin gene-related peptide (CGRP) co-released from the primary sensory fibers have been identified as the key neurotransmitters in pancreas. Pancreatic ductal epithelium cells are one of the important sources of the pancreatic islet β-cell neogenesis. We hypothesized that SP and CGRP might play a role on proliferation of ductal cells and differentiation of ductal cells toward the β-cell neogenesis. Methods Primary ductal cells of rat pancreas at the third passage (P3) were used. The identification of P3 cells were confirmed with flow cytometry analysis and immunostaining by CK19 (the ductal cell marker). Proliferation of ductal cells was verified by CCK-8 assay and Ki67 immunostaining. Differentiation of ductal cells was determined with immunostaining and flow cytometry. Possible mechanism was explored by testing the key proteins of Wnt signaling using Western blot analysis. Results Our data showed that SP but not CGRP promoted proliferation of ductal cells. Moreover, NK-1 receptor antagonist L-703,606 blocked the SP-induced stimulation of proliferation. The results of Western blot analysis showed that L-703,606 attenuated the effects of substance P on NK1R, GSK-3β and β-catenin expression. However, SP did not directly induce the differentiation of ductal cells into β-cells, and did not promote the progression of ductal cells to differentiate into more insulin-produced cells in induction medium. Conclusions These findings suggested that SP but not CGRP promoted proliferation of adult pancreatic ductal cells. SP promoted proliferation of ductal cells but not differentiation into β-cells. NK1R and Wnt signaling pathway might be involved in the mechanism of promoting the proliferation of ductal cells by SP. Findings in this study indicated the lack of SP might be a possible indicator for the initial of diabetes. SP could also be used as a drug candidate for the treatment of diabetes.